When do Online Audiences Amplify Benefits of Self-Disclosure? The Role of Shared Experience and Anticipated Interactivity. Issue 2 (1st May 2020) - Kornfield, Rachel; Toma, Catalina L.
ABSTRACT: As individuals increasingly write about their distressing experiences online, it is important to understand how perceived online audiences influence the effects of self-disclosure. In an experiment, participants wrote about recent breakups for online audiences purportedly varying in 1) whether they shared recent breakup experiences and 2) their ability to leave comments. Participants perceiving audiences with shared experience showed more cognitive processing in their writing and reported increased post-traumatic growth at follow-up than participants perceiving general audiences. Those anticipating comments wrote less about emotions than those who did not. Mechanisms accounting for the benefits of shared experience warrant further investigation.